Preoperative Tunnel Measurement in Hidradenitis Suppurativa: Comparison of Palpation and Ultrasound - Aslı Tatlıparmak; Murat Doğan; Zafer Türkoğlu (Diagnostics)
Background/Objectives: The accurate measurement of tunnel lengths in hidradenitis suppurativa (HS) is critical for surgical planning. This study aimed to evaluate the agreement between palpation and high-frequency ultrasound (USG) for assessing tunnel lengths in HS patients. Methods: This prospective study included patients who underwent the surgical excision of tunnels between May 2024 and July 2024 at a referral dermatology clinic. Tunnel lengths were measured preoperatively using palpation and USG. Clinical and demographic data, including lesion localization and disease severity, were prospectively recorded and analyzed. Results: This study analyzed 121 lesions from patients undergoing surgical excision for HS. Tunnel lengths measured by palpation had a median of 30 mm [IQR 18–40], while USG measurements had a median of 36 mm [IQR 24–51.5], with USG identifying tunnels 10.3 mm longer on average (95% CI: 8.2–12.3). Axillary lesions were most frequent (53.7%), followed by inguinal (32.2%) and sacral regions (6.6%). Most lesions were classified as Hurley stage 2 (59.5%) and stage 3 (37.2%), with a median IHS4 score of 8 [IQR 7–11]. Conclusions: High-frequency USG offers greater precision than palpation in measuring tunnel lengths, indicating its potential to enhance disease assessments in HS.